Dual targeting of DDX3 and eIF4A by the translation inhibitor rocaglamide A. Issue 4 (15th April 2021) - Chen, Mingming; Asanuma, Miwako; Takahashi, Mari; Shichino, Yuichi; Mito, Mari; Fujiwara, Koichi; Saito, Hironori; Floor, Stephen N.; Ingolia, Nicholas T.; Sodeoka, Mikiko; Dodo, Kosuke; Ito, Takuhiro; et al.
Summary: The translation inhibitor rocaglamide A (RocA) has shown promising antitumor activity because it uniquely clamps eukaryotic initiation factor (eIF) 4A onto polypurine RNA for selective translational repression. As eIF4A has been speculated to be a unique target of RocA, alternative targets have not been investigated. Here, we reveal that DDX3 is another molecular target of RocA. Proximity-specific fluorescence labeling of an O -nitrobenzoxadiazole-conjugated derivative revealed that RocA binds to DDX3. RocA clamps the DDX3 protein onto polypurine RNA in an ATP-independent manner. Analysis of a de novo -assembled transcriptome from the plant Aglaia, a natural source of RocA, uncovered the amino acid critical for RocA binding. Moreover, ribosome profiling showed that because of the dominant-negative effect of RocA, high expression of eIF4A and DDX3 strengthens translational repression in cancer cells. This study indicates that sequence-selective clamping of DDX3 and eIF4A, and subsequent dominant-negative translational repression by RocA determine its tumor toxicity. Graphical abstract: Highlights: RocA clamps DDX3 on polypurine sequences in an ATP-independent manner Gln360 in DDX3 is a critical residue for RocA binding RocA⋅DDX3 complex inhibits protein synthesis in a dominant-negative manner eIF4A and DDX3 abundance correlates with RocA sensitivity in cancer cells Abstract : Chen et al. demonstrated the translation inhibitor rocaglamide A (RocA) alternatively targets DDX3, in addition to eIF4A. As RocA converts DDX3 and eIF4A into dominant-negative translational repressors, the abundance of those proteins in cells is an indicator of RocA sensitivity.